A Deletion of the Nuclear Localization Signal Domain in the Fus Protein Induces Stable Post-stress Cytoplasmic Inclusions in SH-SY5Y Cells - Notaro, Antonietta; Messina, Antonella; La Bella, Vincenzo (Frontiers in Neuroscience, 2021)
Mutations in Fused-in-Sarcoma (FUS) gene involving the nuclear localization signal (NLS) domain lead to juvenile-onset Amyotrophic Lateral Sclerosis (ALS). The mutant protein mislocalizes to the cytoplasm, incorporating it into Stress Granules (SG). Whether SGs are the first step to the formation of stable FUS-containing aggregates is still unclear. In this work, we used acute and chronic stress paradigms to study the SG dynamics in a human SH-SY5Y neuroblastoma cell line carrying a deletion of the NLS domain of the FUS protein (homozygous: ΔNLS–/–; heterozygous: ΔNLS+/–). Wild-type (WT) cells served as controls. We evaluated the subcellular localization of the mutant protein through immunoblot and immunofluorescence, in basal conditions and after acute stress and chronic stress with sodium arsenite (NaAsO2). Cells were monitored for up to 24 h after rescue. FUS was expressed in both nucleus and cytoplasm in the ΔNLS+/– cells, whereas it was primarily cytoplasmic in the ΔNLS–/–. Acute NaAsO2 exposure induced SGs: at rescue,>90% of ΔNLS cells showed abundant FUS-containing if compared to less than 5% of the WT cells. The proportion of FUS-positive SGs remained 15–20% at 24 h in mutant cells. Cycloheximide did not abolish the long-lasting SGs in mutant cells. Chronic exposure to NaAsO2 did not induce significant SGs formation. A wealth of research has demonstrated that ALS-associated FUS mutations at the C-terminus facilitate the incorporation of the mutant protein into SGs. We have shown here that mutant FUS-containing SGs tend to fail to dissolve after stress, facilitating a liquid-to-solid phase transition. The FUS-containing inclusions seen in the dying motor neurons might therefore directly derive from SGs. This might represent an attractive target for future innovative therapies.